Radiological diagnosis of Cysticercosis of Breast - An unusual presentation (Indian Journal of Case Reports, 2015)
Breast cysticercosis manifestation is usually uncommon and only a few cases have been reported in the literature. This manifests in the form of signs and symptoms which normally do not point towards the diagnosis. The radiological modalities always narrow down the gap between the complaints and the diagnosis. We present a case with cysticercus cysts in breast parenchyma as well as in both pectoral muscles which was suspected on ultrasonography (USG) and diagnosed on Magnetic Resonance Imaging (MRI). The patient responded to the medical treatment conservatively thus avoiding excisional biopsy. Follow up and repeat MRI has confirmed the cure of the complaints as well as the disease.